Remodelamento do miocárdio no exercício com componente anaeróbico - Verzola, Roberto Mário Machado (Universidade Federal de São Carlos, 2004)
The extracellular matrix (ECM) components are continuously synthesized and degraded at distinct rates in a process called remodeling involving the expression of matrix metallopeptidases (MMPs) and their inhibitors (TIMPs) in physiological (growth, exercise) or pathological (high blood pressure, myocardial infarction) conditions. The expression of myosin heavy chain (MHC) α and β in the myocardium also changes in response to physiological (exercise) and pathological (energy deprivation, hypothyroidism, diabetes mellitus, hypertension) stimulus. The aim of this work was to study the influence of acute swimming training in Wistar male rats (160-180g) for 6hr/day, in 3 sessions of 2 hr each for 1 to 5 consecutive days, on the MMPs and MHC β expression, compared to the sedentary control group. Blood lactate concentration and heart weight/body weight relation were also determined. Heart weight was increased in relation to body weight in the groups that trained for 4 (p<0.05) and 5 days (p<0.01). Blood lactate levels after all training sessions were significantly increased in all days. Morphological analysis showed no alterations or inflammatory signs compared to controls. The expression of MHC β was analyzed by real time RT-PCR showing that it was significantly increased only after 5 days of training (p<0.01). After 4 days, a tendency to increase was observed but it was not significant. Zymography analysis of muscle extracts indicated a single 66kDa activity band that was significantly increased after 3 (p<0.05), 4 and 5 days (p<0.001) and this activity was enhanced in proportion to the duration of training. In conclusion, the heart of small rodents may be biochemical and functionally early conditioned after an acute program of swimming with an anaerobic component.
Keywords: Fisiologia do exercício físico; Remodelamento do miocárdio; Cadeia pesada de miosina; Metalopeptidases de matrizes; Reação em cadeia de polimerase em tempo real; CIENCIAS BIOLOGICAS::FISIOLOGIA